Ticks parasitised feathered dinosaurs as revealed by Cretaceous amber assemblages - Enrique Peñalver (Nature Portfolio, 2017)
Fossils of ticks are rare, and little is known about their ancient hosts. Here, Peñalver and colleagues describe ticks in Cretaceous amber, including representatives of the new family Deinocrotonidae, which are associated with a dinosaur feather and nest biota.